Bacillus megaterium GXU087 secretes indole - 3 - lactic acid to promote soybean growth and nodulation - Qiu, Jingsi; Meng, Xiao’ou; Li, Jingdong; Zhang, Tengfei; Qin, Siying; Li, Yuanfu; Tan, Huihua (Frontiers in Plant Science, 2025)
Bacillus species are recognized as plant growth-promoting bacteria (PGPB), yet the mechanisms behind their crop growth promotion remain elusive. This study is designed to explore the plant growth-promoting (PGP) effects of Bacillus megaterium GXU087 on soybeans and to uncover the underlying mechanism. In vitro, GXU087 exhibited various PGP traits, including phosphate solubilization, nitrogen fixation, production of exopolysaccharide, and biofilm formation. Pot experiments indicated that GXU087 significantly enhanced soybean growth, leading to a remarkable increase in fresh weight (p < 0.05). Additionally, the nodulation parameters of soybeans were improved. Specifically, a 10% concentration of the extracellular extracts from GXU087 exerted a significant promotion on nodulation, with both nodule number and fresh weight parameters increasing significantly (p < 0.05). UPLC-MS analysis verified that GXU087 secreted indole-3-lactic acid (ILA) at a concentration of 232.7 ng/mL. Pot assays further demonstrated that this ILA effectively promoted soybean growth and nodulation within a concentration range of 0.1-10 mg/L. However, exogenous application of ILA did not stimulate rhizobia reproduction, suggesting that bacterial ILA does not promote nodulation by enhancing rhizobia growth. Notably, this is the first report of B. megaterium secreting ILA as a growth and nodulation promoter in soybeans. Our findings offer new insights into the mechanism of B. megaterium action and contribute to the understanding of microbe-induced growth promotion in crops.